Fetal bone development in the lowland paca (Cuniculus paca, Rodentia, Cuniculidae) determined using ultrasonography. Issue 1 (7th April 2020) - da Silva, Gessiane Pereira; Monteiro, Frederico Ozanan Barros; Pereira, Thyago Habner de Souza; de Matos, Sandy Estefany Rodrigues; dos Santos de Andrade, Rafael; El Bizri, Hani Rocha; Coutinho, Leandro Nassar; Valsecchi, João; López-Plana, Carlos; Mayor, Pedro
Abstract: Studying the timing of the main events of embryonic and fetal development may clarify the strategies adopted by species to maximize neonatal survival and the consequences of these events for their life history. This study describes bone development during the fetal phase of the lowland paca ( Cuniculus paca ), comparing it with other precocial or altricial species, and its relationship with the species' adaptive strategies. A total of 102 embryos/fetuses obtained over the course of 17 years through collaboration with local subsistence hunters in the Amazon were analyzed. Measurements of mineralization of the axial and appendicular skeletons were performed by ultrasonography using a 10–18‐MHz linear transducer. The chronological order of occurrence of mineralization in relation to the total dorsal length (TDL) was: skull (TDL = 4.1 cm); vertebral bodies (TDL = 4.6 cm); scapula, humerus, radius, ulna, ilium, ischium, femur, tibia, and fibula (TDL = 6.7 cm); ribs (TDL = 7.8 cm); clavicle (TDL = 8.5 cm); metacarpi/metatarsi (TDL = 11 cm); phalanges (TDL = 15 cm); tarsus (TDL = 18 cm); patella (TDL = 23 cm); and carpus (TDL = 27.2 cm). Secondary ossification centers first appeared in the femoral distal epiphysis (TDL = 16.6 cm) and tibial proximal epiphysis (TDL = 18.4 cm). Advanced fetuses (TDL > 30 cm, 97% gestational period) presented mineralization in all primary and most secondary centers. Compared to other species, paca neonates have a well‐developed skeletal system at birth, which is important for their independent postnatal locomotion. Our results may contribute to the monitoring of bone development in other wild species, helping us to understand their life history, and serving as parameters for comparisons between precocial and altricial mammals. Abstract : Paca neonates have a well‐developed skeletal system at birth compared to altrical species, which is important for independent postnatal locomotion. Advanced fetuses with a TDL of 35.3 cm presented mineralization in primary ossification centers in all evaluated bones of the appendicular skeleton, in both thoracic and pelvic limbs, and in most of the secondary ossification centers during the gestational period.